Correlation between gall bladder fasting volume and postprandial emptying in patients with gall stones and healthy controls. Issue 10 (October 1993) - Pauletzki, J; Cicala, M; Holl, J; Sauerbruch, T; Schafmayer, A; Paumgartner, G
Abstract : To evaluate whether the extent of postprandial gall bladder emptying is correlated with gall bladder fasting volume, gall bladder motility was studied in 56 patients with cholesterol gall stone and 19 control patients. Gall bladder volumes were determined sonographically, while cholecystokinin plasma values were measured radioimmunologically. Twenty three per cent of gall stone patients were classified as pathological contractors (residual fraction > mean +2SD of controls) and 77% as normal contractors. Normal but not pathological contractor patients exhibited larger gall bladder fasting volumes (mean (SEM)) (24.7 (1.7) ml) than controls (15.3 (1.2) ml, p < 0.001). In normal contractor patients and controls fasting volume was closely related with ejection volume (r = 0.97, p < 0.001) and residual volume (r = 0.80, p < 0.001). Although ejection volume was enlarged in normal contractor patients it did not compensate the increase in fasting volume. Thus, residual volumes were considerably increased not only in pathological contractors (12.7 (2.5) ml, p < 0.001) but also in normal contractor patients (7.0 (0.5) v 4.6 (0.6) ml, p < 0.001). Postprandial cholecystokinin secretion did not differ between patients and controls. It is concluded, that in normal contractor patients gall bladder fasting volume is closely correlated with ejection and residual volume. Thus, fasting volume may be an essential factor affecting postprandial gall bladder emptying. Large fasting volumes in cholesterol gall stone disease could thereby contribute to bile retention, which facilitates gall stone growth.